The Role Of Secondary School In Developing A Culture Of Tolerance Among Its Students From The Point Of View Of Teachers (Journal of Hama University, 2025)
The research aimed to reveal the role of secondary school in developing a culture of tolerance among its students from the point of view of teachers in the city of Damascus, as well as to reveal the differences between the averages of the answers of the members of the research sample due to the variables (academic qualification, years of service(,The descriptive analytical method and the questionnaire were used as a tool for collecting data. The research sample included (196) male and female teachers of the general secondary education level in the city of Damascus. The research reached the following results:1- The role of the secondary school in developing a culture of tolerance among its students, from the point of view of teachers in the city of Damascus, has reached a great degree, As for the arrangement of the fields of the questionnaire to identify the role of the secondary school in developing a culture of tolerance, it was as follows: The field (the role of the teacher in developing a culture of tolerance) came in first place and to a large degree, followed by the field (the role of curricula in developing a culture of tolerance) in second place and to a large degree, and finally the field (the role of administration School level in developing a culture of tolerance) ranked third and to a large degree.2- There are no statistically significant differences between the averages of the answers of the research sample members to the questionnaire about the role of the school in developing a culture of tolerance due to the academic qualification variable.3- There are statistically significant differences at the level of significance (0.05) between the averages of the answers of the research sample members to the questionnaire about the role of the secondary school in developing a culture of tolerance due to the variable of years of service, in favor of teachers with the oldest years of service (5 years or more).
Keywords: : Culture Of Tolerance, Secondary School